Deforestation and forest degradation in lowland Bolivia - Pacheco, P. (University of Florida, 2002)
This chapter analyses the causes of deforestation and forest degradation in the Bolivian Amazon. The study predicated on the assumption that the factors involved have less to do with the forest sector itself than with events that take place within the country's political, economic, and social arenas. This paper reviews the situation of land tenure in the Bolivian lowlands and summarises the information about the magnitutes of deforestation and forest degradation until 1985 and followed by the evaluation on the changes in forest cover associated with structural adjustment policies. It concludes that deforestation rates in lowland Bolivia have been relatively low compared to those observed in other countries where tropical forests are found. Recent policies to stimulate the export of soybeans and wood products have had important positive effects. However, long-term benefits could have been greater, and environmental costs could have been lower, if development policies had been linked to initiatives that led to a more equal distribution of land and forest resources.